PATH-07. MULTIPLATFORM MOLECULAR ANALYSES REFINE CLASSIFICATION AND PROGNOSTICATION OF GLIOMAS ARISING IN PATIENTS WITH NEUROFIBROMATOSIS TYPE 1. (14th November 2022) - Lucas, Calixto-Hope; Sloan, Emily; Jung, Jangham; Gupta, Rohit; Wu, Jasper; Vasudevan, Harish; Shai, Anny; Whipple, Nicholas; Bruggers, Carol; Samuel, David; Maher, Ossama; Lu, Rufei; et al.
Abstract: BACKGROUND: Gliomas arising in patients with neurofibromatosis type 1 (NF1) are heterogeneous, occurring from childhood through adulthood, can be histologically low-grade (LG) or high-grade (HG), and follow an indolent or aggressive clinical course. Comprehensive profiling of genetic alterations beyond NF1 and epigenetic classification of these tumors remain limited. METHODS: Next-generation sequencing and DNA methylation profiling was performed on gliomas from 47 NF1 patients and correlated with clinicopathologic features, treatment, and outcomes. RESULTS: 30 tumors demonstrated biallelic inactivation of NF1 without additional oncogenic alterations ("molecular LG subgroup", median age 14 yrs). The remaining 17 tumors harbored additional oncogenic alterations beyond NF1 ("molecular HG subgroup", median age 28), most frequently CDKN2A homozygous deletion (n=13), ATRX mutation (n=8), PIK3CA or PIK3R1 mutation (n=4), and TP53 mutation (n=3). Survival analysis showed significant differences in time to progression (137 vs 11 mos, p< 0.0001) and median survival time (undefined vs 37 mos, p > 0.0001) for molecular LG versus HG subgroups. DNA methylation profiles of the molecular LG subgroup resolved into a new epigenetic cluster closest to but divergent from the three existing reference classes of sporadic pilocytic astrocytoma. DNA methylation profiles of the molecular HG subgroup demonstrated most tumors epigenetically align with either HGAP or various subclasses of IDH-wildtype GBM. CONCLUSION: NF1-associated gliomas stratify into two molecular subgroups. The "molecular LG subgroup" occurs primarily during childhood, harbors biallelic NF1 inactivation only, follows a more indolent clinical course, and has a unique epigenetic signature for which we propose the terminology "pilocytic astrocytoma, arising in the setting of NF1". The "molecular HG subgroup" occurs primarily during adulthood, harbors additional oncogenic alterations including CDKN2A homozygous deletion and ATRX mutation, follows a more aggressive clinical course, and is epigenetically diverse. These findings highlight recurrently altered pathways in NF1-associated gliomas and help inform targeted therapeutic strategies for this patient population.